Variable speed coupling device of oil-electricity hybrid power system - HUANG LIRAN (2022)
The utility model discloses a variable-speed coupling device of an oil-electricity hybrid power system, which is characterized in that a double-planet-carrier structure is arranged in a coupling box body, planet gears and a sun gear are respectively arranged on the double-planet-carrier structure and a middle inner shaft, the planet gears and the sun gear are used for transmission, and the planet gears are meshed with different gear ring structures. Gear transmission output under different transmission ratios is achieved, a brake in a coupling box brakes a gear ring, so that the meshing transmission locking process of different planet gears is achieved, the different gear rings are fixed by jointing the brake, input and output of different power sources, torques and rotating speeds are achieved, the transmission structure is stable, control is stable, and the transmission efficiency is high. An effective coupling structure is provided for dual-output control of the oil-electric hybrid power system, respective